DANA PELAYANAN UMUM: SUDAH REPRESENT ATIFKAH KEBIJAKAN BANTUAN DOMESTIK INDONESIA DI SEKTOR PERT ANIAN? - Sri Nuryanti; Frans B.M Dabukke (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2007)
Domestic Support that included in Green Box is other term of support for farmer in according to agricultural and rural development. So far, developing countries' domestic support is limited. Among General services becomes the most important one among domestic support items. Regarding to competitiveness improvement, domestic support policy is being non-pricefactor of productivity and efficiency improvement. As most budgets are decentralized to local level, gene FaI services becomes important onefor agricultural and rural developments. Nonetheless, necessary to analyze and calculate the magnitude of domestic support which related to general services of green boxfor national and local level. The budget of Indonesian domestic support during 2001-2005 tended to increase. The highest percentage of budget was allocatedfor domesticfood aidfor the needy. Thenfollow by stockholding for food security, general services, and dissaster relief Calculation on wethergeneral services and domestic support budgetfor national level not aggregately accounted local levelyet. The nominal value did not reflect the real allocations. The calculation of green box budget aspart of domestic support has ignored role of general services. General services budget has been most allocated for infrastructure, research, pest and disease control, and promotion and marketing activities. On local level, only 29 per cent budget allocated for general services. Three largest components were allocated for infrastucture, extention, and promotion and marketing activities.